Adaptation of a microsimulation model at the municipality level: demographic and employment evolution in the Altmark region of Germany - İlkay Unay-Gailhard; Omar Baqueiro-Espinosa (SIMULATION, 2015)
Adapting microsimulation models to specific regions is a challenging task. This is especially true when aiming to simulate very low regional levels, such as municipalities, owing to anonymity restrictions or simply nonexistence of data at the required levels. In this study, we present a process to define the dynamics of the PRototypical policy Impact on Multifunctional Activities in rural municipalities (PRIMA) conceptual microsimulation model for the Hohenberg–Krusemark municipality network in the Altmark region of Germany. A parameterization process and the prototypical simulation results of the model are given along with a discussion on the validation of the simulation results by local level stakeholders. The presented technical aspects of the model provide the evolution of the demographic structure and the employment status for individuals living in a set of interconnected municipalities in rural areas. Additional insight was gained by comparing the demographic and employment properties of the simulation results with real data. The comparison allows for the observation of how correctly the model replicates past trends in the municipality network. The model's assumptions are based on the results of a probability table created for the years 2000–2009, and the simulation results are presented for the years 2000–2020.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; agent-based simulation; demographic and employment evolution; Germany; rural areas; municipality